(untitled) (Community Based Medical Journal, 2022)
This cross-sectional, analytical type of study was performed in Department of Anatomy, Dhaka Medical College, Bangladesh, from July 2016 to June 2017 on 52 right hander male and 52 right hander female, 40 left hander male and 34 left hander female Bangladeshi medical students. Convenient purposive sampling technique was adopted. History of any injury of upper limb was excluded to construct standard measurement. Handedness of each medical student was determined by the Edinburgh handedness inventory. Hand breadth and hand length was measured with the help of vernier caliper. Paired and unpaired student‟s „t‟ test and Pearson‟s correlation coefficient test were done for statistical analyses. Handedness score showed nonsignificant positive correlation with right hand shape index (r = +0.087, P>0.05) and left-hand shape index (r = +0.008, P>0.05) in right hander males. Handedness score showed non-significant negative correlation with right hand shape index (r = -0.017, P>0.05) and left-hand shape index (r = -0.003, P>0.05) in right hander females. Handedness score showed non-significant negative correlation with right hand shape index (r= - 0.210, P>0.05) and left-hand shape index (r = -0.247, P>0.05) in left hander males. Handedness score showed non-significant positive correlation with right hand shape index (r= +0.051, P>0.05) and left-hand shape index (r = +0.213, P>0.05) in left hander females. To summarize, handedness score showed nonsignificant positive correlation with right hand shape index and left-hand shape index in right hander males and left hander females. However, handedness score showed non-significant negative correlation with right hand shape index and left-hand shape index in right hander females and left hander males. CBMJ 2022 January: vol. 11 no. 01 P: 14-20